Comparative Evaluation of Incentive Spirometer and Diaphragmatic Breathing Exercise on Pulmonary Function and Functional Capacity in Drivers Exposed to Air-Conditioned and Non-Air-Conditioned Environments (International Journal of Physiotherapy, 2025)
Background: Incentive spirometer (IS) and diaphragmatic breathing exercise (DBE) are simple, non-invasive interventions known to improve lung expansion, enhance ventilation, and strengthen respiratory muscles. To evaluate the effect of the Incentive spirometer and Diaphragmatic breathing exercise on pulmonary function, functional capacity, and perceived exertion in AC and non-AC drivers.Methods: A pre- and post-experimental study was conducted in Urban and rural areas of Tirupati over 12 weeks. This study was conducted with 30 male drivers aged 20–50 years, divided into AC (n = 15) and Non-AC (n = 15) groups using convenience sampling. Anthropometric data (baseline measures such as age, height, weight, and BMI) were collected from all subjects. Pulmonary function (Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV₁), FEV₁/FVC ratio was assessed using a portable spirometer. In contrast, functional capacity was evaluated through the Six-Minute Walk Test (6MWT) distance, and Borg Rate of Perceived Exertion (RPE) was noted. All participants performed the Incentive spirometer and Diaphragmatic breathing exercise for 12 weeks under supervision.Results: Both groups showed significant improvement in pulmonary function and functional capacity (p < 0.05). Non- AC drivers demonstrated greater gains in pulmonary function and walking distance, whereas AC drivers showed a greater reduction in RPE scores.Conclusion: This study on male drivers showed that the incentive spirometer and diaphragmatic breathing exercises significantly improved lung function and 6MWT distance and reduced exertion. Non-AC drivers had greater improvements, highlighting the role of the environment in respiratory adaptation. These findings support the addition of breathing exercises to occupational health programs for drivers.